Tracking Psychodynamic Foci: Trajectories Through the Therapeutic Process - Dagnino, Paula; Calderón, Ana (Frontiers in Psychology, 2022)
Brief psychodynamic psychotherapy has gained importance in current clinical practice. To achieve brevity, a focus must be established and worked through. Different conceptualizations have emphasized the relational patterns and/or conflict foci as central but adopting a mono-schematic approach. However, patients come to treatment with more than one issue that must be addressed. Thus, another focus must be included because of its relevance, i.e. personality functioning. The aims of this study were to identify the presence and depth level of three foci (relational pattern, conflict and personality functioning) in episodes of change throughout the process, and to evaluate the relationship of each focus with the complexity of patients’ change. Initial OPD foci and the presence and depth of each were evaluated in 13 successful brief psychodynamic therapies. Change episodes of those therapies were analyzed as well. Results showed differences between foci in the initial phase with a higher presence of conflict focus). Throughout the process, only the presence and level of personality functioning improved. Also, complexity of patients’ change was related to conflict focus, specifically on the emergence of competence feelings. The results provide evidence and enrich process research of brief psychodynamic therapies.